A Study on the Group Level Workplace Spirituality of the College Teachers with Special Reference to Engineering Colleges in Namakkal District (Global Journal of Management and Business Research, 2016)
The emerging paradigm called 'Workplace Spirituality' is interpreted by many in many ways. The recent researches on 'Workplace Spirituality' reveal that there is a common set of theme that most of the sources agree upon. Most of the researchers in this field use reference from "The Handbook of workplace Spirituality and Organizational Performance" by Giacalone and Jurwierokz (2003). Ashmos and Duchon(2000) describe workplace Spirituality as involving three levels, individual, work-unit and organization-wide. The work-unit dimension (group level) entails how much employees have a sense of connection and community with their management, principal, head of the department, colleagues and students; as well as assessing the extent to which they are caring and encouraging.
Keywords: workplace; spirituality; teachers; interpersonal relationship; engineering college